2016
DOI: 10.4236/ajps.2016.71003
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Relation Oat Panicle with Grain Yield by Nitrogen

Abstract: The oat panicle components were changed by the forms of nitrogen use influencing productivity. The aim of the study was to determine the direct and indirect effects of oat panicle components on grain yield by N-fertilizer rates in succession systems of high and reduced release of N-residual. The study was conducted in the years 2013 and 2014 in a randomized complete block with four replications in a factorial 3 × 2, for nitrogen rates (30, 60 and 120 kg•ha −1) and oat cultivars (Barbarasul and Brisasul) the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
(23 reference statements)
0
26
0
Order By: Relevance
“…Oliveira et al (2011) commentedon the importance of detecting the genetic differences among the oat cultivars in the straw and grains production. The growth and the biomass production in the oat are stronglylinked to the nitrogen availability, index of leaf area, photoperiod, temperature, sun radiation and hydric availability (Almeida et al, 2011;Mantai et al, 2016). Therefore, the use of sustainable and low cost technologies such as the management of vegetation cover, the use of N-residual and the adjustment of the sowing density in oat may favor the straw productivity which returns to the soil on the erosion control, moisture maintenance and protection of the culture in early stage (Silva et al, 2012;Romitti et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al (2011) commentedon the importance of detecting the genetic differences among the oat cultivars in the straw and grains production. The growth and the biomass production in the oat are stronglylinked to the nitrogen availability, index of leaf area, photoperiod, temperature, sun radiation and hydric availability (Almeida et al, 2011;Mantai et al, 2016). Therefore, the use of sustainable and low cost technologies such as the management of vegetation cover, the use of N-residual and the adjustment of the sowing density in oat may favor the straw productivity which returns to the soil on the erosion control, moisture maintenance and protection of the culture in early stage (Silva et al, 2012;Romitti et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…depends, among other factors, on the amount of soil nutrients, the composition of plant residues, the expected desired productivity and humidity, aeration and temperature interaction in cropping systems (Rocha et al, 2008;Romitti et al, 2016). Therefore, the biochemical composition of crop residues used for determining nitrogen mineralization or immobilization may affect the dosages and times of N-fertilizer of the rate of soil nitrogen release and decomposing tissues (Mantai et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is a need to optimize food production from technologies that ensure productivity with reduced costs and sustainability in agricultural ecosystems (Sala et al, 2005;Viola et al, 2013). In this context, several authors have reported the possibility of using nitrogen economically adjusted to the condition of the agricultural year using fractionation to obtain greater efficiency of grain yield (Arenhardt et al, 2015;Espindula et al, 2014;Mantai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Oat is a cereal of multiple purposes, mainly due to the great demand for its derivatives in food production [1] [2]. Oat grains productivity is dependent on the genetic potential of the cultivars, management technologies, climate and favorable soil [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the management technologies, nitrogen plays a decisive role on the productivity of biomass and grains [5] [6]. The new biotypes of oats are highly responsive to the use of nitrogen in the productivity expression [2] [3] [4]. On the other hand, the increase of nitrogen doses, along with favorable meteorological conditions, increases the vegetative development, potentializing lodging [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%